2011
DOI: 10.1007/s00338-011-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemicals produced by Caribbean macroalgae and cyanobacteria have species-specific effects on reef coral microorganisms

Abstract: Coral populations have precipitously declined on Caribbean reefs while algal abundance has increased, leading to enhanced competitive damage to corals, which likely is mediated by the potent allelochemicals produced by both macroalgae and benthic cyanobacteria. Allelochemicals may affect the composition and abundance of coral-associated microorganisms that control host responses and adaptations to environmental change, including susceptibility to bacterial diseases. Here, we demonstrate that extracts of six Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 62 publications
3
73
2
Order By: Relevance
“…Further investigations are needed to determine the direct effects of these interface-associated microbial communities on coral health. Recent studies have shown that different species of algae alter the growth of coral bacteria [61], supporting the hypothesis that algae may directly alter the structure of the coral holobiont.…”
Section: Discussion (A)mentioning
confidence: 64%
“…Further investigations are needed to determine the direct effects of these interface-associated microbial communities on coral health. Recent studies have shown that different species of algae alter the growth of coral bacteria [61], supporting the hypothesis that algae may directly alter the structure of the coral holobiont.…”
Section: Discussion (A)mentioning
confidence: 64%
“…Direct contact with Lobophora macroalgae has already been shown to cause a negative physiological effect on corals in the form of tissue necrosis and bleaching (7,9,14,15,47,48). Previous studies have also shown that crude extracts from Caribbean L. variegata, particularly hydrophilic compounds, have broadspectrum antibacterial activity that causes significant shifts in coral-associated microbial communities (13,21). Thus, while most other studies have focused on lipophilic organic compounds from macroalgae, the current study builds on previous microbial community profiling data (21) and further indicates that aqueous compounds produced by Lobophora sp.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that Porites cylindrica was the most resistant to macroalgal damage based on visual assessments (9). Direct contact between macroalgae and corals has been implicated in reduced coral growth and fecundity, bleaching, tissue necrosis, mortality, and disease (7)(8)(9)(10)(11)(12)(13)(14)(15). Macroalgae have also been shown to indirectly induce and inhibit coral larval settlement (16,17), both of which are likely to result in larval mortality via poor substratum choice (e.g., shading, overgrowth, and ephemeral growth), mechanical damage (e.g., algal abrasion), or allelochemical defenses.…”
mentioning
confidence: 99%
See 2 more Smart Citations